5.4k views
17 votes
Use the power reduction formulas to rewrite the expression. (Hint: Your answer should not contain any exponents greater than 1.)

sin^4 (4x)

1 Answer

8 votes

The formulas in question are

sin²(x) = (1 - cos(2x))/2

cos²(x) = (1 + cos(2x))/2

Then

sin⁴(4x) = (sin²(x))²

… = ((1 - cos(2x))/2)²

… = (1 - 2 cos(2x) + cos²(2x))/4

… = (1 - 2 cos(2x) + (1 + cos(4x))/2)/4

… = 1/4 - 1/2 cos(2x) + (1 + cos(4x))/8

… = 3/8 - 1/2 cos(2x) + 1/8 cos(4x)

User Hectorcanto
by
7.6k points